Diversification as an effective business strategy / Baderisang Mohamed and Siti Nurhidayu Sharin - Mohamed, Baderisang; Sharin, Siti Nurhidayu (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
There are several strategies available for businesses to fulfill the organizations’ objectives, aims or goals such as the integration, intensive, diversification and defensive strategies. Selecting the best suitable business strategies for the company based on their respective aim is very important because not all strategies can be used for a certain specific aim.